The research into the development of passenger transport by land - Butkevičius, Jonas (Transport, 2004)
This is the first scientific work in Lithuania carrying out a complex research into passenger transport by land, covering all problematic issues related to the field such as development, market planning, organization, management, competition, contractual relations, financing, development of transport technologies, implementation of new transport technologies elaborating the theoretical base for the development of passenger transport. The research shows the analysis of the movement of passenger transport volumes and determines the regularity of these changes. The forecast of passenger transport by land is based on a multiple analysis. The work determines the perspective markets of rail and road transport as well as elaborates the principles of the improvement of road and rail transport interaction. The author originates the principles of the development of passenger transport technologies and the principles of the implementation of advanced technologies. The author also founds the principles of planning, organization and management of land transport as well as the principles of security of equal conditions of competition and contractual relations between customers and haulers.First Published Online: 27 Oct 2010